2012
DOI: 10.1177/1078345811436000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric Disorders in the Texas Juvenile Correctional System

Abstract: Most studies assessing the burden of psychiatric disorders in juvenile correctional facilities have been based on small or male-only samples or have focused on a single disorder. Using electronic data routinely collected by the Texas juvenile correctional system and its contracted medical provider organization, we estimated the prevalence of selected psychiatric disorders among youths committed to Texas juvenile correctional facilities between January 1, 2004, and December 31, 2008 (N = 11,603). Ninety-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 24 publications
2
35
1
1
Order By: Relevance
“…Despite the fact that the DPS screening results should, if anything, overestimate the true prevalence of disorders in the sample, the present estimates Screening Outcomes Among Justice-Involved Youth 221 tended to be lower than those drawn from samples of detained youth and adolescents (overall estimates ranging from 56% to 98%, Cauffman, 2004;Colins et al, 2010;Fazel et al, 2008;Harzke et al, 2012;Stoddard-Dare, Mallett, & Boitel, 2011;Teplin, Welty, Abram, Dulcan, & Washburn, 2012;Vermeiren et al, 2006). The present study is more in line with the Wasserman et al (2005) study of youths at probation intake, which found that 45.7% screened positive for at least one disorder on the DISC.…”
Section: Prevalence Estimatescontrasting
confidence: 52%
“…Despite the fact that the DPS screening results should, if anything, overestimate the true prevalence of disorders in the sample, the present estimates Screening Outcomes Among Justice-Involved Youth 221 tended to be lower than those drawn from samples of detained youth and adolescents (overall estimates ranging from 56% to 98%, Cauffman, 2004;Colins et al, 2010;Fazel et al, 2008;Harzke et al, 2012;Stoddard-Dare, Mallett, & Boitel, 2011;Teplin, Welty, Abram, Dulcan, & Washburn, 2012;Vermeiren et al, 2006). The present study is more in line with the Wasserman et al (2005) study of youths at probation intake, which found that 45.7% screened positive for at least one disorder on the DISC.…”
Section: Prevalence Estimatescontrasting
confidence: 52%
“…The second most common type was the inattentive type with a rate of 33.3% (n=24), and the least common type was the hyperactive type (5.6%, n=4). A recent metaanalysis 25 pointed out that the most commonly seen subtype of ADHD is the combined type, as was also found in studies from North Carolina, 9 Colombia, 12 Brazil, 38,39 Italy, 8 Majorca, 11 Venezuela, 15 Texas, 13 Saudi Arabia, 10 Lebanon, 40 and Turkey. 21 Conversely, ADHD prevalence studies from Nigeria 41,42 and a prevalence study from Brazil 43 reported that the inattentive type was the most common subtype.…”
Section: Discussionmentioning
confidence: 91%
“…31 A review of the worldwide epidemiological studies on ADHD prevalence revealed a wide range of prevalence's, ranging from 0.9% to 20%. [8][9][10][11][12][13][14][15][16][17] Some studies have attributed the wide variation in ADHD prevalence to cultural and geographical factors, while many others have advocated that these discrepancies result from the diagnostic systems and methodology used, sources of information, and whether the diagnostic criteria (impairment and involving at least two domains) are required. 14 We used strict DSM-IV-TR diagnostic criteria for ADHD of symptoms being observed in at least two environments, a symptom onset before the age of 7 years, and a minimum symptom duration of 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Young and Thome (21) reported that 45% of youth and 24% of adult male offenders had a childhood history of ADHD, and 14% continued to be symptomatic into adulthood. Similarly, in a large study, prevalence of ADHD was 18.3% of 11,603 adolescents committed to Texas juvenile correctional facilities between 2004 and 2008 (27). Furthermore, a systematic review on the epidemiology of psychiatric disorders among male detained adolescents reported a mean ADHD prevalence of 13.5% (19).…”
Section: Epidemiology Of Adhd Among Offendersmentioning
confidence: 93%